Prevalence of depressive symptoms among schoolchildren in Cyprus: a cross-sectional descriptive correlational study. Issue 1 (December 2017) - Sokratis, Sokratous; Christos, Ζilides; Despo, Panagi; Maria, Karanikola
Abstract Background Depressive symptoms in the young constitute a public health issue. The current study aims to estimate: (a) the frequency of depressive symptoms in a sample of final grade elementary-school children in Cyprus, (b) the association among frequency of depressive symptoms, gender and nationality and, (c) the metric properties of the Greek-Cypriot version of the children's depression inventory (CDI). Methods A descriptive cross-sectional study with internal comparison was performed. The occurrence of depressive symptoms was assessed with the CDI, which includes 5 subscales: depressive mood, interpersonal difficulties, ineffectiveness, anhedonia and negative self-esteem. Clinical depressive symptoms were reported as CDI score ≥19. CDI was anonymously and voluntarily completed by 439 schoolchildren [mean age 12.3 (±0.51) years old] from fifteen public elementary schools (217 boys and 222 girls), yielding a response rate of 58.2%. The metric properties of the CDI were assessed in terms of internal consistency reliability and construct validity via exploratory factor analysis (rotated and unrotated principal component analysis). Descriptive and inferential statistics were explored. Results 10.25% of Cypriot schoolchildren reported clinical depressive symptoms (CDI score ≥19). Statistically significant differences were reported between boys and girls in all five subscales of the CDI. Girls reported higher scores in "Depressive mood", "Negative self-esteem" and "Anhedonia" subscales, while boys scored higher in "Interpersonal difficulties" and "Ineffectiveness" subscales. There were no statistically significant differences among ethnicity groups regarding the entire CDI or the subscales of it. Concerning the metric properties of the Greek-Cypriot version of the CDI, internal consistency reliability was adequate (Cronbach's alpha = 0.84). Factor analysis with varimax rotation resulted in five factors explaining 42% of the variance. Conclusions The Greek-Cypriot version of the CDI is a reliable tool for the assessment of the severity of depressive symptoms in schoolchildren. Institutional counseling services, as well as interventions aiming to empower the young need to address the different psychological needs of boys and girls. Longitudinal studies within this cultural context may be warranted, with special attention to other factors related to depressive symptoms and low self-esteem in schoolchildren, such as suicidality or bullying.